The Influence of Specific Job Satisfaction Dimensions on Turnover Intention Among Educators in Putrajaya - Karim, Amir Faisal Abdul; Vasudevan, Hemaloshinee (Yayasan Sembilan Pemuda Indonesia, 2025)
HRM practices and policies significantly influence employee satisfaction levels and turnover intentions. Organizations prioritize job satisfaction for employees, as human resources significantly impact growth and competitiveness, making them stand out from the competition. The study examined the relationship between job satisfaction and turnover intention in the public education sector, examining factors such as work-life balance, job security, career growth, reward, and emotional intelligence. In this study, the convenient sampling, a non-probability sampling method, was employed to efficiently collect data. A total of 201 questionnaires were created and distributed to public educators in the Federal Territory of Putrajaya. The data was analyzed using SPSS software to determine if there were significant differences between the variables. All hypotheses (H1-H5) were supported and this research enhances theoretical understanding, fills knowledge gaps, and serves as a foundation for future research in organizational behaviour and human resource management. This study provides insights for developing and reshaping policies on work-life balance, job satisfaction, career growth, rewards, recognition, and emotional intelligence.